Morphometric characteristics, hygienic behavior and aggressiveness ofnative bees Apis mellifera sp. - Vásquez Arca, Olinda Carmen Rosa (2015)
This research aimed to evaluate the morphometric characteristics, hygienic behavior and temperament of native bees (Apis mellifera sp.) of Lambayeque due to there is very few investigations on these characteristics in our country. lt was used the descriptive method, evaluating eight morphometric variables, obtaining an average weight 0.008g, bee length 14.00 mm, chest length 3.96mm, abdomen length 8.04 mm, forewing length 9.24 mm, hindwing length 6.63 mm, femur length 2.38 mm, and tibia length 3.07 mm. The temperament of bees was evaluated too using a subjective rating scale, finding a 13.33% of little docile hives, a 33.33% of aggressive bees and 53.33% of very aggressive bees, a characteristic temperament of native bees. Hygienic behavior was evaluated using the breeding puncture obtaining as a result, slightly hygienic hives an average of71.75% removal of cells with dead brood.